Substantial iodine volume load reduction in CT angiography with dual-energy imaging: insights from a pilot randomized study - Carrascosa, Patricia (2014)
We explored whether dual-energy computed tomography (DECT) can allow a significant reduction in iodinated contrast volume during computed tomography angiography (CTA) without hampering image quality or assessibility. We prospectively randomized patients clinically referred to CTA to single energy computed tomography (SECT) with full iodine volume load (group A), DECT with 50 % iodine volume load (group B), DECT with 40 % iodine volume load (group C), and DECT with 30 % iodine volume load (group D); and compared image quality and assessibility. Eighty patients were enrolled and prospectively randomized. The mean age was 61.7 ± 15.0 years and 56 (71 %) patients were male. The demographical characteristics, body mass index, or mean radiation dose did not differ between groups. Significant reductions in total contrast volume were achieved in groups B, C, and D; with mean administrated contrast volumes of 90.3 ± 10.1, 39.5 ± 4.6, 28.3 ± 6.5, and 23.9 ± 6.0 mL, respectively, in groups A to D (p < 0.0001). With regard to image quality, no significant decrease in the Likert scale was observed with reductions of up to 60 % of the contrast volume (groups B and C). DECT at 50–60 keV in association with up to 60 % iodine load reduction, allowed similar signal density, image noise, and signal to noise ratio that SECT imaging with full iodine load. In this pilot, prospective, randomized study, dual energy CTA with up to 60 % iodine volume load reduction provided similar image quality and assessibility than full iodine load with conventional SECT imaging.